Ah, let's paint a happy little picture with this equation. To find the x-intercept, we set y to 0 and solve for x. So, -10x = -20, which gives us x = 2. For the y-intercept, we set x to 0 and solve for y. So, -10y = -20, which gives us y = 2. And just like that, we've found our x-intercept at (2, 0) and y-intercept at (0, 2).
4x-10y=11 4x=11+10y 10y+11=4x 10y=4x-11 y=(4/10)x-(11/10) y=(2/5)x-(11/10)
x + 2y = 10At the x-intercept, y=0:x = 10At the y-intercept, x=0 ==> 2y = 10y = 5
Write out equation - 10y - 5x= - 20 Negate equation 10y + 5x = 20 Isolate y variable 10y = - 5x + 20 Divide equation by 10 y= -1/2x + 2
(y - 8)(y - 2)
Y-8x plus 9y equals 10y-8x.
y - intercept = 10x - intercept = -10y- intercept: x = 0y = x + 10y = 0 + 10y = 10x - intercept: y = 0y = x + 100 = x + 10x + 10 = 0x = -10
10x-10y = 0
y + x = 9 10y + 20x = 100 This is a basic linear system of equalities. We can start by rewriting the first equation as: -10y - 10x = -90 by multiplying the equation by -10, from here we can eliminate y and solve for x (-10y - 10x = -90) + (10y + 20x = 100) = (10x = 10) This yields x = 1, and by plugging x into the first equation y = 8
X=7 y=5
Basically, the x-intercept is what x equals when y=0, and the y-intercept is what y equals when x=0. To find the x intercept, set y equal to 0. -5x+10(0)=20 -5x+0=20 -5x=20 divide both sides by -5 x=-4 so the x intercept is (-4,0) To find the y intercept, set x equal to 0. -5(0)+10y=20 0+10y=20 10y=20 divide both sides by 10 y=2 so the y intercept is (0,2)
y = 0.5x - 0.3
It is: y = -0.4x+1 when in slope intercept form.
4x-10y=11 4x=11+10y 10y+11=4x 10y=4x-11 y=(4/10)x-(11/10) y=(2/5)x-(11/10)
10x+10y+100 There is a common 10 in each number. 10(x+y+10)
x + 2y = 10At the x-intercept, y=0:x = 10At the y-intercept, x=0 ==> 2y = 10y = 5
The y-intercept means... When does the line cross through the y-axis?This happens when the x-value is zero... so simply just plug in zero for "x"y = 2 * (0) + 10y = 10y-intercept is equal to 10For the x-intercept just make the y-value equal to zero.
+13x +10y -3x -4ysimplified is+10x +6y.I think this write but not really he use the method write